The Effect of Education on Quality of Life of Breast Cancer Patients With Family Assistance and Treatment Compliance As A Mediation Variable - Rolianna Harianja; Kemala Rita Wahidi; Rina Mutiara (Syntax Corporation Indonesia, 2022)
Breast cancer is the most common type of cancer compared to other types of cancer. Breast cancer can have a psychological impact from the early diagnosis. In addition, the side effects of cancer modality therapy can also affect the psychology of patients and families. The purpose of this study was to analyze the effect of providing education on the quality of life of breast cancer patients with family assistance and medication adherence as mediating variables at the